if a=2+√3, then find value of a-1/a
Answers
Answered by
1307
Heya friend,
Here is the answer you were looking for:
![a = 2 + \sqrt{3} \\ \\ \frac{1}{a} = \frac{1}{2 + \sqrt{3} } \\ a = 2 + \sqrt{3} \\ \\ \frac{1}{a} = \frac{1}{2 + \sqrt{3} } \\](https://tex.z-dn.net/?f=a+%3D+2+%2B++%5Csqrt%7B3%7D++%5C%5C++%5C%5C++%5Cfrac%7B1%7D%7Ba%7D++%3D++%5Cfrac%7B1%7D%7B2+%2B++%5Csqrt%7B3%7D+%7D++%5C%5C+)
On rationalizing the denominator we get,
![\frac{1}{a} = \frac{1}{2 + \sqrt{3} } \times \frac{2 - \sqrt{3} }{2 - \sqrt{3} } \\ \frac{1}{a} = \frac{1}{2 + \sqrt{3} } \times \frac{2 - \sqrt{3} }{2 - \sqrt{3} } \\](https://tex.z-dn.net/?f=+%5Cfrac%7B1%7D%7Ba%7D++%3D++%5Cfrac%7B1%7D%7B2+%2B++%5Csqrt%7B3%7D++%7D+++%5Ctimes++%5Cfrac%7B2+-++%5Csqrt%7B3%7D+%7D%7B2+-++%5Csqrt%7B3%7D+%7D++%5C%5C+)
Using the identity :
![(x + y)(x - y) = {x}^{2} - {y}^{2} (x + y)(x - y) = {x}^{2} - {y}^{2}](https://tex.z-dn.net/?f=%28x+%2B+y%29%28x+-+y%29+%3D++%7Bx%7D%5E%7B2%7D++-++%7By%7D%5E%7B2%7D+)
![\frac{1}{a} = \frac{2 - \sqrt{3} }{ {(2)}^{2} - {( \sqrt{3} )}^{2} } \\ \\ \frac{1}{a} = \frac{2 - \sqrt{3} }{4 - 3} \\ \\ \frac{1}{a} = 2 - \sqrt{3} \\ \\ a - \frac{1}{a} \frac{1}{a} = \frac{2 - \sqrt{3} }{ {(2)}^{2} - {( \sqrt{3} )}^{2} } \\ \\ \frac{1}{a} = \frac{2 - \sqrt{3} }{4 - 3} \\ \\ \frac{1}{a} = 2 - \sqrt{3} \\ \\ a - \frac{1}{a}](https://tex.z-dn.net/?f=+%5Cfrac%7B1%7D%7Ba%7D++%3D++%5Cfrac%7B2+-++%5Csqrt%7B3%7D+%7D%7B++%7B%282%29%7D%5E%7B2%7D++-+%7B%28+%5Csqrt%7B3%7D+%29%7D%5E%7B2%7D+%7D++%5C%5C++%5C%5C+++%5Cfrac%7B1%7D%7Ba%7D++%3D++%5Cfrac%7B2++-++%5Csqrt%7B3%7D+%7D%7B4+-+3%7D++%5C%5C++%5C%5C++%5Cfrac%7B1%7D%7Ba%7D++%3D+2+-+++%5Csqrt%7B3%7D++%5C%5C++%5C%5C+a+-++%5Cfrac%7B1%7D%7Ba%7D+)
Putting the values,
![a - \frac{1}{a} = (2 + \sqrt{3} ) - (2 - \sqrt{3} ) \\ \\ a - \frac{1}{a} = 2 + \sqrt{3} - 2 + \sqrt{3} \\ \\ a - \frac{1}{a} = \sqrt{3} + \sqrt{3} \\ \\ a - \frac{1}{a} = 2 \sqrt{3} a - \frac{1}{a} = (2 + \sqrt{3} ) - (2 - \sqrt{3} ) \\ \\ a - \frac{1}{a} = 2 + \sqrt{3} - 2 + \sqrt{3} \\ \\ a - \frac{1}{a} = \sqrt{3} + \sqrt{3} \\ \\ a - \frac{1}{a} = 2 \sqrt{3}](https://tex.z-dn.net/?f=a+-++%5Cfrac%7B1%7D%7Ba%7D++%3D+%282+%2B++%5Csqrt%7B3%7D+%29+-+%282+-++%5Csqrt%7B3%7D+%29+%5C%5C++%5C%5C+a+-++%5Cfrac%7B1%7D%7Ba%7D++%3D+2+%2B++%5Csqrt%7B3%7D++-+2+%2B++%5Csqrt%7B3%7D++%5C%5C++%5C%5C+a+-++%5Cfrac%7B1%7D%7Ba%7D++%3D++%5Csqrt%7B3%7D++%2B++%5Csqrt%7B3%7D++%5C%5C++%5C%5C+a+-++%5Cfrac%7B1%7D%7Ba%7D++%3D+2+%5Csqrt%7B3%7D+)
Hope this helps!!!
Feel free to ask in the comment section if you have any doubt regarding to my answer...
@Mahak24
Thanks...
☺☺
Here is the answer you were looking for:
On rationalizing the denominator we get,
Using the identity :
Putting the values,
Hope this helps!!!
Feel free to ask in the comment section if you have any doubt regarding to my answer...
@Mahak24
Thanks...
☺☺
nancyyy:
wah mahak wah ^_^"
Answered by
17
Answer:
a - =2√3
Step-by-step explanation:
Given,
a = 2+√3
To find,
a -
Solution:
a = 2+√3
=
The rationalizing factor is 2 -
=
=
= 2 - √3
a - = 2+√3 - (2-√3)
= 2+√3 - 2+√3
=2√3
∴a - =2√3
#SPJ2
Similar questions
Computer Science,
8 months ago
Political Science,
8 months ago
Biology,
8 months ago
English,
1 year ago
Math,
1 year ago
English,
1 year ago